Non-Operative Treatment of Intraabdominal Hemorrage due to Warfarin Use: Two Patient Reports - Barut, Bora; Ince, Volkan; Koc, Cemalettin; Yonder, Huseyin; Dirican, Abuzer; Ates, Mustafa (Annals of Medical Research, 2021)
None
Keywords: Warfarin; Intraabdominal Hemorrhage; Non-Operative Treatment.